A parametric study into the influence of strain hardening slope on the stability and collapse responses of steel tubes under compressive loading. (October 2021) - Nazari, A.R.; Taheri, F.
Abstract: The influence of the material strain-hardening response on the plastic stability of the moderately thick stainless-steel and mild-steel tubular columns is studied. A parametric study on the strain-hardening slope of the material σ-ε; curve is presented to exhibit variation of the load-carrying capacity in the tubes. The mechanism of the so-called elephant's foot plastic buckling mode is discussed. The load-carrying capacity and post-yield response of a couple of representative tubes, examined by experiments, are also simulated using the finite element method (FEM), thereby validating the integrity of the incorporated numerical framework. The framework is used to examine the load-carrying performance of the tubes with various D/t ratios. The results produced by the parametric study are used to investigate a collapse index for the prediction of the ultimate load-carrying capacity of the tubes. Useful results about the collapse state of the tubes with different D/t are obtained by focusing separately on the various segments of the material sequential softening after yield point. The results highlight the significance of each segment of the post-yield portion of σ-ε; curve on the load-carrying capacity of various tubular columns. For example, this study shows that for a case study (tube with D/t = 30) by doubling the slope of the later segment of the strain-hardening region in the σ-ε; curve, one can expect a significant increase (as high as 111%) in the energy absorption capacity prior to collapse threshold state (CTS). In contrast, a moderate increase of only 17% shall be expected in columns with D/t = 60 when the same level of change to the strain-hardening slope is considered.